Evaluation method for surface treatment fillers
Patent Information
- Application Number
- JP2021160283
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-09-30
AI Technical Summary
【0014】 本発明の評価方法によれば、簡便に表面処理フィラーの充填性を評価することが可能となる。これにより、例えば、従来よりも効率的な品質管理が可能となる。
Smart Images

Figure 0007645758000001 
Figure 0007645758000002 
Figure 0007645758000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel method for evaluating a surface-treated filler, and more particularly to a method for evaluating the fillability of a surface-treated filler in a resin by measuring the surface potential of the particles with a scanning probe microscope. [Background technology]
[0002] Resin composite materials, which are made by combining inorganic fillers and resins, are used in a wide range of fields. In order to improve the compatibility between the inorganic filler and the resin, it is common to use inorganic fillers that have been surface-treated (surface-treated fillers). By performing surface treatment, the filling ability of the inorganic filler into the resin is improved, making it easier to produce resin composite materials in which the inorganic filler is uniformly dispersed in the resin.
[0003] The surface treatment of inorganic fillers is achieved by reacting inorganic fillers that have not been surface-treated (untreated fillers) with a surface treatment agent, thereby forming a coating derived from the surface treatment agent on the surfaces of the particles.
[0004] Here, even if a surface treatment operation is performed, if the surface treatment is not performed appropriately, for example, if the distribution of the coating is not uniform and there are parts on the particle surface of the surface-treated filler that are not sufficiently surface-treated, the filling ability of the surface-treated filler into the resin may not be sufficiently improved. Therefore, in the production of surface-treated fillers, it is important to check whether the surface treatment of the obtained surface-treated filler is performed appropriately, and in particular to evaluate the uniformity of the coating, in situations such as considering the surface treatment conditions and quality control.
[0005] As a method for evaluating the surface treatment state of a surface-treated filler, for example, the methods proposed in Patent Documents 1 to 3 have been disclosed.
[0006] Patent Document 1 discloses a method for evaluating the surface treatment state of a surface-treated filler by heating the filler to burn off the coating material derived from the surface treatment agent, which is an organic substance, and measuring the thermal changes that occur during this process.
[0007] Patent Document 2 discloses a method for evaluating the surface treatment state by observing the change in pH when acid is dropped into a suspension of a surface-treated filler (magnesium hydroxide). This method is said to be able to accurately evaluate the coating state because the more uniform the surface treatment and the less exposed surface of the particles, the faster the rate of pH decrease.
[0008] In Patent Document 3, it is said that by immersing a surface-treated filler that has been surface-treated with a silane coupling agent (surface treatment agent) in alcohol, an alcohol having an alkoxy group in the silane coupling agent is generated, and this is quantified by gas chromatographic analysis, the reaction process and reaction rate between the particles and the silane coupling agent can be quantitatively and accurately evaluated.
[0009] However, in the conventional evaluation methods such as those described in Patent Documents 1 to 3, it is difficult to evaluate the distribution of the coating on a single surface-treated particle, and the evaluation of the uniformity of the coating is insufficient. Therefore, in order to know the filling property of the surface-treated filler with high accuracy, the only way was to actually fill it into a resin, and if the resin was changed, it was necessary to perform the evaluation again, which was time-consuming. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2001-85806 A [Patent Document 2] JP 2003-83950 A [Patent Document 3] JP 2004-108932 A Summary of the Invention [Problem to be solved by the invention]
[0011] As described above, in the conventional evaluation method of surface-treated fillers, it is difficult to sufficiently evaluate the filling property taking into account the uniformity of the coating on the particle surface, and it is difficult to evaluate the filling property of the surface-treated filler simply and with high accuracy. Therefore, the present invention aims to provide a simple and highly accurate evaluation method of surface-treated fillers. [Means for solving the problem]
[0012] The present inventors conducted intensive research to solve the above problems, and as a result, discovered that it is possible to evaluate the distribution of coating by measuring the surface potential of the surface-treated particles in a surface-treated filler with a scanning probe microscope, and that this makes it possible to easily and accurately evaluate the filling property of the surface-treated filler.
[0013] That is, the present invention is a method for evaluating a surface-treated filler, which is characterized by including a step of measuring the surface potential of surface-treated particles in a surface-treated filler by a scanning probe microscope. Preferably, the method further includes a step of measuring the surface potential of untreated particles in an untreated filler corresponding to the surface-treated filler, and / or a step of measuring the surface potential of a surface treatment agent corresponding to the surface-treated filler. Effect of the Invention
[0014] According to the evaluation method of the present invention, it is possible to easily evaluate the filling property of the surface-treated filler, which enables, for example, more efficient quality control than conventional methods. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In this specification, an inorganic filler that has been surface-treated with a surface treatment agent is referred to as a "surface-treated filler", and an inorganic filler before the surface treatment of the surface-treated filler or an inorganic filler produced under the same manufacturing conditions is referred to as an "untreated filler corresponding to the surface-treated filler" (sometimes simply referred to as an "untreated filler"). Furthermore, particles in a surface-treated filler are referred to as "surface-treated particles", and particles in an untreated filler are referred to as "untreated particles". The organic matter derived from the surface treatment agent present on the surface of the surface-treated particles is referred to as a "coating", and the raw material for forming the coating is referred to as a "surface treatment agent corresponding to the surface-treated filler" (sometimes simply referred to as a "surface treatment agent").
[0016] The surface-treated filler evaluated by the evaluation method of the present invention is not particularly limited, and for example, the evaluation method of the present invention can be applied to surface-treated silica, alumina, aluminum nitride, boron nitride, etc. The particle size of the surface-treated filler is not particularly limited, but since a small particle size makes evaluation difficult and a large particle size requires a long time for evaluation, the particle size is preferably 0.5 μm to 100 μm, and more preferably 1.0 μm to 10 μm.
[0017] The surface treatment agent is not particularly limited, and known agents can be used, such as silane coupling agents. The surface treatment agent preferably has a difference in surface potential between the surface treatment agent and the untreated inorganic filler of 100 mV or more, more preferably 120 mV or more. As described later, the greater the difference in surface potential between the surface treatment agent and the untreated inorganic filler, the easier it is to evaluate the surface-treated filler with high accuracy.
[0018] A scanning probe microscope is a device that evaluates the surface condition of a measurement object by scanning a probe along the surface of the measurement object and detecting the interaction between the probe and the measurement object. The measurement of the surface potential by a scanning probe microscope involves applying a DC voltage to the measurement sample to charge it, then applying an AC voltage to the probe to scan the sample surface and detect the electrostatic force acting between the sample and the probe, thereby measuring the surface potential at each position of the measurement object. Since the surface potential of a surface-treated particle is usually different between the part where a coating is present and the part where no coating is present, by measuring the surface potential of the particle with such a scanning probe microscope, it becomes possible to distinguish between the part where a coating is present and the part where no coating is present on the particle surface. This makes it possible to evaluate the state of the coating on the particle surface. The surface potential of the surface-treated filler is evaluated by appropriately picking up and measuring the surface-treated particles in the surface-treated filler. There is no particular limit to the number of surface-treated particles to be picked up, but since the evaluation accuracy can be improved by measuring a larger number of particles, it is preferable that the number of particles is 5 or more per 500 g of filler, and more preferably 10 or more.
[0019] The scanning probe microscope used in the evaluation method of the present invention is not particularly limited as long as it is capable of measuring the surface potential of particles.
[0020] The type of the probe used in the evaluation method of the present invention is not particularly limited as long as it can measure the surface potential of the particle, but in order to obtain high resolution, it is preferable that the radius of curvature of the probe tip is 5 to 100 nm. It is also preferable to use a probe tip with a conductive coating on the tip, and examples of the conductive coating include Au coating, Pt coating, PtIr coating, PtSi coating, and diamond coating.
[0021] In the evaluation method of the present invention, the method of placing the measurement sample on the scanning probe microscope is not particularly limited as long as the above measurement can be performed, but for example, after dispersing particles in a volatile solvent to prepare a dispersion liquid, the dispersion liquid is dropped onto a conductive substrate, and the measurement substrate prepared by volatilizing the volatile solvent is fixed to the sample stage of the scanning probe microscope using a conductive paste. The volatile solvent is not particularly limited as long as it can disperse the particles to be measured and does not react with the particles, and for example, alcohols such as methanol, ethanol, propanol, isopropyl alcohol, and butanol, ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone, ethers such as diethyl ether, dioxane, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, and tetrahydrofuran, alkanes such as hexane, 2-methylpentane, heptane, cyclohexane, octane, 2,2,4-trimethylpentane, and petroleum ether, esters such as ethyl formate, butyl formate, ethyl acetate, propyl acetate, and butyl acetate, benzene, toluene, xylene, and naphthalene can be used. The conductive substrate may be, for example, a highly oriented pyrolytic graphite (HOPG) substrate, a conductively coated mica substrate, etc. The conductive paste may be one in which conductive particles are dispersed in a resin, such as one in which silver particles, gold particles, platinum particles, etc. are dispersed in an epoxy resin.
[0022] In the evaluation method of the present invention, a DC voltage is applied to the particles to be measured to charge them, and then the surface of the sample is scanned while applying an AC voltage to the probe, and the electrostatic force acting between the sample and the probe is detected. To achieve this, it is first necessary to obtain a topographical image (height image) of the particle by scanning the surface of the particle to be measured with the probe. There are no particular limitations on the method for obtaining the topographical image, but it can be performed, for example, by a tapping mode method in which the probe is vibrated to scan the sample surface.
[0023] Tapping mode is a method in which a cantilever with a probe attached to the tip is vibrated at the resonant frequency to scan the particle surface. Measurements in tapping mode can obtain not only topographical images, but also phase images of the particle surface. It is believed that the phase image can also be used to estimate the distribution of coatings, and by combining it with surface potential measurements, it is expected that a lot of information about surface-treated fillers can be obtained, making it one of the preferred methods for obtaining topographical images.
[0024] Next, a DC voltage is applied to the particles to be measured to charge them. The conditions for applying the DC voltage are not particularly limited as long as the voltage is within a range that allows a good observation image to be obtained. For example, the applied voltage may be 100 to 1000 mV.
[0025] Thereafter, while applying an AC voltage to the probe, a scanning position is determined based on data of the topography image of the particle to be measured, and the probe is scanned while the sample stage and the probe are electrically connected so as to obtain a surface potential image, and the electrostatic force acting between the sample and the probe is detected, thereby making it possible to measure the surface potential of the particle. The scanning position is not particularly limited as long as it can be performed at a position where the probe and the particle do not come into contact with each other and where an electrical connection between the sample and the probe can be obtained, but since the shorter the distance between the probe and the particle, the higher the sensitivity is but the more difficult it is to adjust the probe position, in the present invention, the position of the probe is preferably controlled to 5 nm to 300 nm from the surface of the particle, and more preferably controlled to 50 nm to 200 nm.
[0026] In the evaluation method of the present invention, the distribution of surface potential on the particle surface can be measured by scanning the probe over the entire surface of the particle and measuring the surface potential at each position using the above-mentioned method. From this distribution of surface potential, the distribution of the coating can be evaluated.
[0027] Although it is not clear why the surface treatment state of particles can be evaluated by the evaluation method of the present invention, the inventors speculate as follows. That is, since the surface potential of untreated particles and the surface potential of a surface treatment agent are usually different, the surface potential of a portion of a surface-treated particle where a coating of the surface treatment agent is present will be different from that of an untreated particle. Therefore, it is presumed that it becomes possible to evaluate the state of the coating on the particle surface by the surface potential.
[0028] The filling property of the surface-treated filler can be evaluated based on the surface potential, for example, from a histogram showing the frequency of the surface potential. Specifically, the evaluation can be performed based on, for example, the most frequent value of the surface potential in the histogram.
[0029] When evaluating by the mode of surface potential, if the type of untreated filler and the type of surface treatment agent are the same, it can be said that there is a correlation between the filling property and the mode of surface potential, so that evaluation can be made from this. For example, if the surface potential of a surface-treated filler whose filling property is known is measured in advance and the mode of surface potential at which high filling property is obtained is grasped, the surface potential of a newly manufactured surface-treated filler is measured and the mode is obtained, so that the filling property of the filler can be easily predicted.
[0030] When the surface potential of the untreated filler corresponding to the surface-treated filler is also measured, more detailed information can be obtained, which is a preferred embodiment. For example, when comparing an untreated filler and a surface-treated filler using the same surface treatment agent, the greater the difference between the mode of the surface potential of the surface-treated filler and the mode of the surface potential of the untreated filler, the more sufficiently the surface treatment is performed, the more uniform the distribution of the coating is, and the better the filling property can be evaluated.
[0031] The surface potential of the surface-untreated filler may be measured according to the above-mentioned method for measuring the surface potential of particles. In addition, when the surface potential of the surface treatment agent is also measured, it is also possible to evaluate the filling property by comparing the mode of the surface potential of the surface treatment agent with the mode of the surface potential of the surface treatment filler. For example, when comparing an untreated filler with a surface-treated filler using the same surface treatment agent, the closer the difference between the mode of the surface potential of the surface-treated filler and the mode of the surface potential of the surface treatment agent is, the more sufficiently the surface treatment is performed, the more uniform the distribution of the coating is, and the better the filling property can be evaluated.
[0032] The surface potential of the surface treatment agent may be measured by placing a surface treatment agent measurement sample on a scanning probe microscope and measuring it in the same manner as for particles. The surface treatment agent measurement sample may be prepared, for example, by dropping a solution prepared by dissolving the surface treatment agent in a volatile solvent onto a conductive substrate and volatilizing the volatile solvent. The volatile solvent is not particularly limited as long as it can measure the surface potential of the surface treatment agent, and may be, for example, alcohols such as methanol, ethanol, propanol, isopropyl alcohol, and butanol; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone; ethers such as diethyl ether, dioxane, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, and tetrahydrofuran; alkanes such as hexane, 2-methylpentane, heptane, cyclohexane, octane, 2,2,4-trimethylpentane, and petroleum ether; esters such as ethyl formate, butyl formate, ethyl acetate, propyl acetate, and butyl acetate; benzene, toluene, xylene, and naphthalene. The conductive substrate may be a conductive substrate equivalent to that used when measuring particles.
[0033] The evaluation method of the present invention makes it possible to evaluate the filling property of the surface-treated filler without actually filling it into a resin. Therefore, by using the evaluation method of the present invention, it becomes possible to easily evaluate the manufactured surface-treated filler, which contributes to simplifying the inspection. EXAMPLES
[0034] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The samples used for evaluation are as follows.
[0035] Aluminum Nitride Powder A1: Aluminum nitride powder (non-surface-treated aluminum nitride powder, average particle size 1 μm, manufactured by Tokuyama Corporation) · B1 to 3: A1 treated with an alkyl silane coupling agent S1 according to the following surface treatment method. Note that B1 to 3 differ in the amount of silane coupling agent used in the surface treatment. · C1 to 3: A1 treated with a methacrylic silane coupling agent S2 according to the treatment method below. Note that C1 to 3 differ in the amount of silane coupling agent used in the surface treatment. D1 to D3: A1 treated with epoxy-based silane coupling agent S3 according to the following treatment method. Note that D1 to D3 differ in the amount of silane coupling agent used in the surface treatment. · E1 to 3: A1 treated with a phenyl-based silane coupling agent S4 according to the treatment method below. Note that E1 to 3 differ in the amount of silane coupling agent used in the surface treatment.
[0036] <Surface treatment method for aluminum nitride powder> 500g of aluminum nitride powder A1, a specified amount of silane coupling agent, and 600g of isopropyl alcohol were placed in a glass eggplant flask and stirred with a fluororesin stirring blade for 30 minutes. After removing the isopropyl alcohol under reduced pressure using a rotary evaporator, the mixture was dried under reduced pressure at 100°C to obtain a surface-treated aluminum nitride powder. The obtained surface-treated aluminum nitride powder weighed about 500g.
[0037] <Measurement of the surface potential of filler> 0.005 g of filler and 10 g of ethanol were placed in a 50 mL screw tube, and ultrasonic waves were applied for 15 minutes in an ultrasonic bath to prepare a sample dispersion. The prepared sample dispersion was collected with a dropper, and one drop was dropped onto a 10 mm square HOPG substrate, and then the substrate was dried at 80°C to remove the ethanol to obtain a measurement substrate. The measurement substrate obtained was fixed to the sample stage of a scanning probe microscope (Bruker: Dimension Icon) using a conductive paste (silver particles dispersed in epoxy resin). Next, particles with a particle size of 1 μm to 10 μm were selected, and a roughness image of the particles was obtained by tapping mode. Next, the applied voltage was set to 500 mV, and the distance between the probe and the particle was set to 100 nm, and the surface potential of the particles was measured. The probe used had a tip curvature radius of 25 nm and was coated with Pt-Ir. The same procedure was carried out for 20 particles, and from the results of all the measured particles, a histogram was obtained with the horizontal axis representing the surface potential and the vertical axis representing the frequency, and the most frequent value of the surface potential was determined.
[0038] <Surface potential measurement of surface treatment agent> A drop of the silane coupling agent was collected with a dropper and dropped onto a 10 mm square HOPG substrate, which was then heated at 100°C to obtain a measurement substrate. The measurement substrate obtained was fixed to the sample stage of a scanning probe microscope (Bruker: Dimension Icon) with conductive paste. Next, the amplitude and gain of the vibrating probe were adjusted so that a topographical image could be obtained. Next, the applied voltage was set to 500 mV, the distance between the probe and the particle was set to 100 nm, and the surface potential of the particle was measured. The probe used had a tip curvature radius of 25 nm and was coated with Pt-Ir. From the measurement results, a histogram was obtained with the horizontal axis representing the surface potential and the vertical axis representing the frequency, and the most frequent value of the surface potential was obtained.
[0039] <Evaluation of filling properties of filler> The two-liquid addition reaction type silicone resin and the filler were kneaded using a foam remover (Thinky Corporation) and the maximum filler loading amount was confirmed to evaluate the filler loading ability. The evaluation results are shown in order of the maximum filler loading amount.
[0040] <Example 1> According to the measurements of the surface potential of the above fillers and surface treatment agents, the surface potentials of fillers A1, B1 to B3, and surface treatment agent S1 were obtained. In addition, the loading property of B1 to B3 was evaluated. As shown in Table 1, the results indicate that the loading property is higher as the mode of the surface potential of the surface-treated filler moves away from the mode of the surface potential of the untreated filler (A1) and approaches the mode of the surface potential of the silane coupling agent (S1).
[0041] [Table 1]
[0042] <Example 2> According to the measurements of the surface potential of the above fillers and surface treatment agents, the surface potentials of fillers A1, C1 to C3, and surface treatment agent S2 were determined. In addition, the loading property of C1 to C3 was evaluated. As shown in Table 1, the results indicate that the loading property is higher as the mode of the surface potential of the surface-treated filler moves away from the mode of the surface potential of the untreated filler (A1) and approaches the mode of the surface potential of the silane coupling agent (S2).
[0043] [Table 2]
[0044] <Example 3> According to the measurements of the surface potential of the above fillers and surface treatment agents, the surface potentials of fillers A1, D1 to D3, and surface treatment agent S3 were determined. In addition, the loading property of D1 to D3 was evaluated. As shown in Table 1, the results indicate that the loading property is higher as the mode of the surface potential of the surface-treated filler moves away from the mode of the surface potential of the untreated filler (A1) and approaches the mode of the surface potential of the silane coupling agent (S3).
[0045] [Table 3]
[0046] <Example 4> According to the measurements of the surface potential of the above fillers and surface treatment agents, the surface potentials of fillers A1, E1 to E3, and surface treatment agent S4 were obtained. In addition, the loading property of E1 to E3 was evaluated. As shown in Table 1, the results indicate that the loading property is higher as the mode of the surface potential of the surface-treated filler moves away from the mode of the surface potential of the untreated filler (A1) and approaches the mode of the surface potential of the silane coupling agent (S4).
[0047] [Table 4]
[0048] From the above, it was shown that there is a correlation between the surface potential of the surface-treated filler and the filling ability of the surface-treated filler in a resin, and that the filling ability of the filler can be evaluated by measuring the surface potential of the surface-treated filler with a scanning probe microscope.
Claims
[Claim 1] A method for evaluating the filling property of a surface-treated filler into a resin, comprising a step of measuring the surface potential of particles of the surface-treated filler and particles of an untreated filler and / or a surface treatment agent corresponding to the surface-treated filler using a scanning probe microscope, and is characterized by comparing the most frequent values of the surface potential in a histogram showing the frequency of the surface potential of the particles of the surface-treated filler and particles of an untreated filler and / or a surface treatment agent corresponding to the surface-treated filler.
Citation Information
Patent Citations
Method for inspecting surface-treated state of filler for resin of wiring board, treatment method, and the wiring board.
JP2001085806A
Method for evaluating surface covering state in magnesium hydroxide based flame retarder
JP2003083950A
Method for evaluating reaction rate of silane coupling agent used for surface treatment of inorganic filler
JP2004108932A
Toner and method of manufacturing the same
JP2015141220A
Toner for electrostatic latent image development
WO2017168863A1